Immersive digital heritage experience with the use of interactive technology - Ioannides, Marinos; Athanasiou, Vasilis; Chatzigrigoriou, Pavlos; Papageorgiou, Eirini; Leventis, Georgios; Nikolakopoulou, Vasiliki; Sovis, Christian (My University, 2016)
This paper presents alternative methodologies for disseminating information that derives from a holistic documentation of a monument with the use of interactive technologies. These technologies are incorporated within an interactive book, while the book’s context is about the unique monument Panagia of Asinou church in Nicosia (Cyprus). The prototype of the interactive book has been developed at a previous stage as an experimental educational tool. In this phase the prototype will be further developed in order to incorporate all the multimedia data collected about the monument and demonstrate them in a userfriendly way. Moreover, it will be adequately evaluated by specific target groups of users and experts. The goal is to be installed at the church of Asinou and provide the visitors of the church with an amazing immersive experience.
Keywords: Education; Immersive experience; Interactive books; Interactive technology; Kinect; Motion sensor; Projection